2010
DOI: 10.1016/j.jfoodeng.2009.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Use of galactomannan edible coating application and storage temperature for prolonging shelf-life of “Regional” cheese

Abstract: a b s t r a c tThe objectives of this work were to determine the influence of the application of two different coatings (galactomannan and chitosan) and of storage temperature on the gas exchange rate of ''Regional" cheese; subsequently, the coating that showed the greatest influence on the cheese gas exchange and simultaneously decreased the O 2 consumption ðR O 2 Þ and the CO 2 production ðR CO 2 Þ rates was applied on cheese, being the shelf-life parameters monitorized through the performance of chemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 24 publications
7
60
0
5
Order By: Relevance
“…Then, 37 days was reported as the last sampling time. Cerqueira et al (2010) found statistically lower counts (P < 0.05) for total mould/yeast and mesophilic bacteria counts in Saloio cheese coated with galactomannan when compared to the uncoated cheeses, stored at 20°C, but these differences disappeared when the samples were stored at 4°C. These results are in agreement with those observed in this work, where the effectiveness of the chitosan-natamycin coating was demonstrated when the cheeses were inoculated with moulds and stored at 25°C, temperature at which the microorganisms grow faster.…”
Section: Cheese Analysesmentioning
confidence: 81%
“…Then, 37 days was reported as the last sampling time. Cerqueira et al (2010) found statistically lower counts (P < 0.05) for total mould/yeast and mesophilic bacteria counts in Saloio cheese coated with galactomannan when compared to the uncoated cheeses, stored at 20°C, but these differences disappeared when the samples were stored at 4°C. These results are in agreement with those observed in this work, where the effectiveness of the chitosan-natamycin coating was demonstrated when the cheeses were inoculated with moulds and stored at 25°C, temperature at which the microorganisms grow faster.…”
Section: Cheese Analysesmentioning
confidence: 81%
“…The coating was successful for prolonging the shelf life of Fuji apple wedges by 2 weeks of storage compared with the control apple slices which showed shelf life of less than 4 days. In another study, Cerqueira et al (2010) coated a commercial semi-hard cheese with a galactomannan coating and observed that the cheese shelf life was improved as the coating decreased the O 2 consumption and the CO 2 production rates, enhancing the weight and appearance. The authors finally remarked that coating can be used to incorporate natural preservatives to reduce post contamination.…”
Section: Gumsmentioning
confidence: 99%
“…Regional (semi-hard) cheese was coated with solutions of chitosan (0.5% chitosan, 2% glycerol/sorbitol), and galactomannan extracted from Gleditsia triacanthos seeds (1.5% galactomannan, 2.0% of glycerol and 0.5% of corn oil) stored at different temperature and the rate of gas exchanges were followed [11]. Cheese coated with galactomannan showed the highest decrease in gas exchange, decreased moisture content (2.5 and 1.9%) and weight losses (3.8 and 3.1% at storage temperature of 4 and 20°C, respectively.…”
Section: Coating With Biopolymer Solutionsmentioning
confidence: 99%